Praktik Storytelling Digital dalam Konten TikTok Transpakuan sebagai Media Komunikasi Publik - Roshinta Nurfajaristi; Hudi Santoso (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This research is motivated by the increasing use of social media as a means of public communication that demands the delivery of information in an interesting, informative manner, and able to build audience engagement. This study aims to analyze the construction of storytelling elements, the function of storytelling, and the role of digital storytelling practices in increasing the effectiveness of public communication in Transpakuan TikTok content. The study uses a descriptive qualitative approach with data collection techniques through in-depth interviews and observation of Transpakuan TikTok content. The research informants consisted of four people who have roles in managing Transpakuan's communication and social media. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that digital storytelling practices in Transpakuan TikTok content are built through structured content planning by utilizing elements of hooks, storylines, conflicts, solutions, and Call To Action (CTA). The function of storytelling is not only as a means of conveying information about public transportation services, but also as an educational and persuasive medium that is able to connect institutional messages with the audience's daily experiences. The research findings show that content that displays user experiences, service operational activities, and passenger problem solving tends to generate higher audience engagement than conventional informative content. Digital storytelling practices have been proven to increase the effectiveness of public communication by enhancing engagement and emotional connection with audiences, as well as strengthening Transpakuan's image as a communicative, responsive, and adaptable public transportation service to digital media developments. Therefore, digital storytelling plays a crucial role in strengthening communication between institutions and the public.